Comparative Analysis of DNA Barcodes in The Fabaceae Family - Tsany, Haura Fikriyyah; Indriyani Roslim, Dewi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
In identifying plants, people are confused about choosing the appropriate barcode for identification. For that reason, this study aims to analyze four DNA barcode rbcL, matK, trnL-trnF IGS, and ITS in the Fabaceae family. DNA sequence were taken and collected from Genbank through the NCBI website, which is 30 species from 6 genera each consisting of 5 species and the outgroup (Acacia auriculiformis). DNA sequence analysis was performed using MEGA 11. Phylogenetic analysis were performed using the Neighbor Joing Tree (NJ) and Maximum Likehood (ML) methods. The results of the analysis sequence variation showed that the highest conserved site was found in rbcL (83.72%) and variable site was found in ITS (62.03%). The number of segregation sites, substitution rates and diversity values in the Fabaceae family were highest in the ITS, respectively (451), (0.155284), and (0.219148). In conclusion, the four DNA barcodes analyzed in the Fabaceae family, namely rbcL, matK, trnL-trnF IGS and ITS, were able to separate the genera in the Fabaceae family. Among the four DNA barcodes analyzed, ITS was superior in identifying the Fabaceae family. The results of this study can be used as information in identifying plants in the Fabaceae family.